MEMBANGUN MODEL PERLINDUNGAN HUKUM TERHADAP MASYARAKAT SEBAGAI KORBAN PENCEMARAN DAN/ATAU PERUSAKAN LINGKUNGAN OLEH KORPORASI DENGAN PRINSIP RESTORATIVE JUSTICE - Widowaty, Yeni; Fitriyanti, Fadia (Jurnal Media Hukum, 2014)
Due to pollution and environmental destruction that most feel  is  the victim. Most victims also suffered losses, both material  and  immaterial  losses,  therefore  it  is  natural  that  the  victims  should  receive protection.  The purpose of  this  research  is  to  analyze  about:  1)  the  resolution  of  environmental  cases which  occur  either through the courts or out of court; 2)  the implementation of legal protection for  the victims of pollution and environmental destruction; 3)  formulating  the  ideal model of legal protection for  the victims of pollution and environmental destruction by the corporation is based on the principles of restorative justice in the future. The research method  is used  the  socio-legal  research using primary and  secondary data. The  results  showed  that environmental cases can be  resolved through the court and outside the court. Ideal model of  legal protection for the  victims of pollution and  / or environmental destruction by the  corporation  is based on  the  restorative justice principle in the future.The offender in this case as the corporation will deal with victims of environmental pollution and the state  as a facilitator. The  Facilitator from  the state for this early stage could be  represented by a judge. In an agreement between  the perpetrator and the victim of the most important is the provision of compensation  from  the  offender  to  the  victim. Ideally  in  the  concept  forward  on major  and  compensation mechanism  is  stipulated  in  the  rules of  implementation.